Single gene, two diseases, and multiple clinical presentations: Biotin-thiamine-responsive basal ganglia disease - Kılıç, Betül; Topçu, Yasemin; Dursun, Şiar; Erol, İlknur; Dolu, Merve Hilal; Taşdemir, Haydar Ali; Aydın, Kürşad (Elsevier, 2020)
Aim: To present seven new genetically confirmed cases of biotin-thiamin-responsive basal ganglia disease (BTBGD) with different clinical and brain magnetic resonance imaging (MRI) characteristics. Material and methods: Genetic variants, clinical presentations, brain MRI findings, treatment response, and prognosis of seven selected patients with BTBGD, diagnosed with SLC19A3 mutations were described. Results: Among seven patients diagnosed with BTBGD, two had early infantile form, four had classic childhood form, and one was asymptomatic. Four different homozygous variants were found in the SLC19A3. Two patients with early infantile form presented with encephalopathy, dystonia, and refractory seizure in the neonatal period and have different variants. Their MRI findings were similar and pathognomonic for the early infantile form. Three siblings had same variants: one presented seizure and encephalopathy at the age of 4 months, one presented seizure at 14 years, and another was asymptomatic at 20 years. Only one of them had normal MRI findings, and the others MRI findings were similar and suggestive of the classic form. Other two siblings; one of them presented with developmental delay, seizure, and dystonia at 18 months and the other presented with subacute encephalopathy and ataxia at 20 months. Their MRI findings were also similar and suggestive of the classic form. Conclusion: BTBGD may present with dissimilar clinical characteristics or remain asymptomatic for a long time period even in a family or patients with same variants. Brain MRI patterns may be important for the early diagnosis of BTBGD that would save children's lives.
Keywords: SLC19A3; Thiamine; Biotin; Clinical Presentation; MRI Patterns